Etiket Era Baru Berbasis Muatan Lokal untuk Produk Unggulan “Batik Heritage Laweyan” Siap Ekspor - Sayekti, Pranti; Irawanto, Rudi (Indonesian Journal for Social Responsibility, 2023)
This community service activity which is carried out in the form of training aims to provide skills to Mahkota Laweyan Small and Medium Industries (IKM) in designing new era batik etiket based on local content, especially for superior products "Laweyan Heritage Batik" ready for export. Mahkota Laweyan is one of the IKMs in Kampoeng Batik Laweyan which produces eco-friendly batik. Currently, Mahkota Laweyan has 17 employees who generally handle batik production and marketing. Now, Mahkota Laweyan has 12 types of batik products that have been patented and have fulfilled SNI. Products that have met the Indonesian National Standard have the right to use the collective mark held by the Kampoeng Batik Laweyan Development Forum (FPKBL). However, these patented batik products still do not have a label to display the brand on each type of product. Even though the brand is needed to introduce the product to the wider community. IKM Kampoeng Batik Laweyan, including the Mahkota Laweyan, is tasked with preserving Laweyan cultural products, one of which is etiket which is becoming extinct. Therefore, for the sake of exporting and preserving cultural products, it is necessary to design labels based on local content, not only to fulfill marketing purposes but also to revitalize labels as cultural products. The function of etiket is to carry the brand name, represent products that have a good reputation, and bring local Laweyan content to be introduced in the domestic and foreign markets. The design of a new era of etiket based on local content is carried out with assistance. Etiket batik that has been designed is then applied to batik products for marketing purposes both online and offline marketing.